Computerized Tomography of the Otic Capsule and Otoliths in the Toadfish, Opsanus tau. - Edds-Walton, P.; Arruda, J.; Fay, R.; Ketten, Darlene (John Wiley and Sons Inc (wiley online library), 2015)
The neurocranium of the toadfish (Opsanus tau) exhibits a distinct translucent region in the otic capsule (OC) that may have functional significance for the auditory pathway. This study used ultrahigh resolution computerized tomography (100 µm voxels) to compare the relative density of three sites along the OC (dorsolateral, midlateral, and ventromedial) and two reference sites (dorsal: supraoccipital crest; ventral: parasphenoid bone) in the neurocranium. Higher attenuation occurs where structural density is greater; thus, we compared the X-ray attenuations measured, which provided a measure of relative density. The maximum attenuation value was recorded for each of the five sites (x and y) on consecutive sections throughout the OC and for each of the three calcareous otoliths associated with the sensory maculae (lagena, saccule, and utricle) in the OC. All three otoliths had higher attenuations than any sites in the neurocranium. Both dorsal and ventral reference sites (supraoccipital crest and parasphenoid bone, respectively) had attenuation levels consistent with calcified bone and had relatively small, irregular variations along the length of the OC in all individuals. The lowest relative attenuations (lowest densities) occurred consistently at the three sites along the OC. In addition, the lowest attenuations measured along the OC occurred at the ventromedial site around the saccular otolith for all seven fish. The decrease in bone density along the OC is consistent with the hypothesis that there is a low-density channel in the skull to facilitate transmission of acoustic stimuli to the auditory endorgans of the ear. J. Morphol. 276:228-240, 2015. © 2014 Wiley Periodicals, Inc